Satukan Langkah Kecil Bersama Keindahan Dan Hangatnya Berbagi Civitas Akademika Universitas Merdeka Surabaya Pada Panti Asuhan Al-Huda Karah Kota Surabaya - Clara Sarti Widiwati; Tisa Angelia; Ikamto Budiman; I Komang Kerthajaya (Asthadarma : Jurnal Pengabdian Kepada Masyarakat, 2024)
The purpose of this service is to develop the potential of the members of the Al-Huda Karah Orphanage in Surabaya City and to become a means of friendship between Lecturers and Students of Merdeka University of Surabaya with the Management and Members of the Al-Huda Karah Orphanage in Surabaya City. The implementation was carried out by the Al-Huda Karah Orphanage in Surabaya City. Education is a social process in which an organized environment such as school and home, can influence a person to develop attitudes and behavioral skills in themselves and in society. Education is carried out through 2 things, namely formal and non-formal education. Formal education is education through schools or universities. Non-formal education is education through reading books and learning through the experiences of others.